Elaboration of an Optimal Scheme for the Use of Substitution Therapy for Diffusion Toxic and Endemic Goiter After the Thyroidectomy - Hikmatov J.S; Sulaymonov J.O; Axrorova L.B (Zien Journals, 2022)
As a result of research of 32 patients with a diffusion and toxic and multinodal craw by which the total tireoidektomiya is carried out, from early postoperative complications at 5 patients tranzitor hypoparatiroziz was observed, and at 4 of them against application of preparations of calcium and vitamin D these signs completely regressed. The hypothyroidism was observed at all patients. Purpose of replacement therapy is an obligatory component in postoperative treatment of a diffusion and toxic and multinodal toxic craw and is carried out under strict supervision of an endosurgeon and the endocrinologist
Keywords: diffusion toxic goiter; endemic goiter; thyroidectomy; substitution therapy